The Periosteal Autografts Transplantation for Cartilage Defects of the Hip in Older Children With Developmental Dysplasia as an Adjunctive Procedure. Issue 17 (April 2016) - Du, Ming-Hua; Ding, Yu; Shi, Xian; Xu, Rui-Jiang
Abstract : Abstract: Cartilage lesions are at a high prevalence in dysplastic hips and may relate to arthritic changes and hip joint dysfunction. To date, the effectiveness of repair of articular cartilage defects in the dysplastic hips has not yet been thoroughly evaluated. Here we retrospectively reviewed the effects of acetabuloplasty procedures with/without concomitant autologous tibial periosteal transplantation (ATPT) for articular cartilage defects of the hip in older children with developmental dysplasia of the hip (DDH). Older DDH children with focal cartilage defects of the acetabular or femoral cartilage or both in the hip joint were treated by acetabuloplasty procedures with (Group I) or without (Group II) concomitant ATPT to evaluate the improvements in range of motion (ROM), pain relief of hip, walking tolerability (WL), radiologic evaluations, and outcomes in the long-term follow-up. More satisfactory functional outcome is readily achieved among patients treated with combined acetabuloplasty and ATPT, evidenced by marked pain relief and improved ROM and WL. The latest favorable radiologic evaluation was 70.6% in Group I and 60.0% in Group II, respectively. More hips exhibited congruency between the femoral head and the shell, with less deformity of femoral head and acetabulum or narrowed joint space in Group I. Few major complications were recorded in Group I. Application of periosteal autograft for repair of cartilage defects within the hip joint might be an effective adjunctive treatment for acetabuloplasty in preventing stiffness, reducing pain, and improving ROM and outcomes in hip rehabilitation in the long-term follow-up in older children with DDH.